The Impact of Sports Injuries on Athlete Performance - Khairani, Azahra; Farhanah, Shafazila Nisa; Nurfauziah, Erika; Setiawan, Muhammad Arief; Aulia, Dany (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Injuries that occur to a person's body during exercise are caused by physical activity that can cause injury, disability, or damage to muscles or joints, as well as other parts of the body, Injuries that occur to a person's body while exercising doing certain exercises, sports injuries are not only rapid damage that occurs during exercise, such as strains on the body's soft tissues, but also overuse syndrome, which is caused by continuous exercise with inconsistent movements or postures that cause clinical symptoms, Such as functional overreaching or non-functional overreaching is used to describe the performance or performance of athletes or athletes. This condition affects the healing process and the training load on the athlete. In addition, overtraining syndrome is divided into two clinical categories: sympathetic and parasympathetic. More than 50% of athlete injuries involve the lower extremities, and on average sports injuries occur more during matches than during training, An athlete's recovery process takes longer If this is not handled properly, it will hurt the athlete's performance.